Towards developing a Healthcare Situation Monitoring Method for Smart City Initiatives: A Citizen Safety Perspective - Miah, Shah J; Vu, H. Quan (Australasian Journal of Information Systems, 2020)
Research in Smart City development has been proliferated over the past few years, which focused heavily on various supporting service sectors, such as healthcare. However, little effort has been made to design health surveillance support systems, which is also important for the advancement of public healthcare monitoring as an essential smart city initiatives. From an information system (IS) design perspective, this paper introduces a social media-based health surveillance supporting method, which can automatically extricates relevant online posts for health symptom management and prediction. We describe and demonstrate an IS design approach in this paper for hay-fever prediction solution concept based on Twitter posts. This concept can be applicable to fully functional solution design by relevant practitioners in this field.